Ndspdatpupw coaxial phase change fiber membrane, preparation method and application thereof

CN122899008APending Publication Date: 2026-10-13CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610973555.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0007]本发明的目的在于针对现有技术的不足,提供一种NDs@PDA/TPU/PW同轴相变纤维膜及其制备方法和应用,解决了现有有机相变材料易泄露、热导率低、功能单一等问题,具有优异力学性能、紫外阻隔、防水抗污和光热转换性能,适用于穿戴式防护、光热转换及能量管理等领域

Benefits of technology

(1)本发明基于同轴静电纺丝技术,实现了金刚石、TPU及相变材料正十八烷在空间、热学与力学维度上的深度协同:外壳层致密且连续的TPU聚合物网络提供宏观的物理限域作用,将内核相变材料约束在一维微纳通道内。与此同时,内核层中引入的微纳米金刚石利用其多孔/表面活性位点,通过界面毛细管作用力对熔融态的PCM分子进行微观吸附与位阻限域。通过这种“同轴宏观外壳限域+核内金刚石微观锚定”的空间三维协同机制,该复合膜在有效封装率达到40%负载,能够抑制PCM在相变过程中的宏观相分离,有效解决了液态渗漏难题,赋予了材料优异的封装效率与热循环稳定性。同时,纤维膜具备优异的热循环稳定性,经50次热循环后相变潜热基本不变。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122899008A_ABST
    Figure CN122899008A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of functional fiber materials, and particularly discloses a NDs@PDA / TPU / PW coaxial phase change fiber membrane as well as a preparation method and application thereof. Nano-diamonds are dispersed in a mixed solvent of tetrahydrofuran and N,N-dimethylformamide, and then thermoplastic polyurethane is added into the above solution to prepare NDs@PDA / TPU shell spinning solution, and PW is used as core layer spinning solution; secondly, the coaxial electrostatic spinning technology is used to control the core-shell propulsion speed, the PW is encapsulated in the NDs@PDA / TPU shell layer, and the coaxial phase change diamond composite fiber membrane with excellent ultraviolet blocking, phase change heat storage and photo-thermal conversion performance is obtained after drying. The melting temperature of the coaxial fiber membrane is about 28.20 DEG C, which is in the human thermal comfort range; the melting enthalpy is as high as 95.23 J / g, and the ultraviolet shielding performance UPF is greater than 12000.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional fiber materials technology, and relates to an NDs@PDATPUPW coaxial phase change fiber membrane, its preparation method and application. Background Technology

[0002] With the rapid development of microelectronic integration technology, the widespread adoption of high-power-density wearable electronic devices, and the rise of multifunctional smart textiles, the problem of transient heat accumulation during device operation is becoming increasingly serious. If high-flux-density heat cannot be dissipated in time, it will lead to thermal degradation of electronic components, shorten their lifespan, and severely reduce the comfort and safety of human wearers. Therefore, developing novel temperature-controlling materials that combine efficient thermal management capabilities with excellent mechanical flexibility has become an important research direction in materials science and microelectronic thermal control.

[0003] Phase change materials (PCMs) utilize the latent heat absorption or release during phase transitions at specific temperatures to achieve temperature regulation and energy storage, showing broad application prospects in the field of flexible temperature control. However, conventional organic PCMs (such as higher alkanes, polyethylene glycol, and solid paraffin) have the following drawbacks in practical applications: First, after a solid-liquid phase transition, they transform into flowing liquids, which, in the absence of microscopic constraints, are prone to macroscopic material leakage and loss, not only damaging the structural integrity of the material but also easily causing short circuits in electronic devices or environmental pollution; second, their intrinsic thermal conductivity is usually below 0.3 W / (m·K), resulting in excessive thermal conduction resistance of the internal lattice and a lag in thermal response rate, failing to meet the transient heat dissipation requirements of high-power devices.

[0004] To achieve shape fixation and leak-proof properties in phase change materials (PCMs), coaxial electrospinning technology has been extensively studied. This technology enables the integrated fabrication of composite fibers with a clear "core-shell" structure at the micro-nano scale using a coaxial composite nozzle. Typically, thermoplastic polyurethane (TPU), with its good film-forming properties and strong mechanical toughness, is used as the shell framework to provide macroscopic physical coating, while the PCM serves as the core layer for heat storage. However, existing polyurethane-based coaxial electrospun PCM membranes still face the following bottlenecks in practical preparation and application: (1) Imbalance between thermal conductivity and thermal storage performance, and poor process continuity. To improve the thermal conductivity of fiber membranes, conventional techniques attempt to introduce high aspect ratio thermally conductive fillers such as carbon nanotubes and graphene into coaxial fluids. However, under the high-voltage electric field and high-shear flow field of electrospinning, high aspect ratio carbon-based fillers are prone to anisotropic viscosity increases, local abnormal concentration of electric field, and imbalance of interfacial tension in the narrow flow channel of the coaxial needle, thereby causing process failures such as instability of the coaxial Taylor cone, frequent nozzle blockage, or flow interruption in the core-shell structure. In addition, carbon-based fillers have intrinsic conductivity and dark color, which limits their application in insulating microelectronic devices or multi-color smart clothing.

[0005] (2) The contradiction between high encapsulation efficiency and thermo-mechanical bonding force at the core-shell interface. Increasing the actual loading of the phase change material in the core layer is key to obtaining a high phase change enthalpy (large heat storage capacity). However, under high loading conditions where the effective encapsulation efficiency of the phase change material reaches about 40%, the existing coaxial spinning process suffers from high interfacial thermal resistance due to the lack of effective physical / chemical interfacial anchoring force between the phase change material molecules in the core layer and the inner wall of the polyurethane in the outer shell. After undergoing multiple solid-liquid thermal cycles, the molten phase change material is prone to volume expansion stress concentration in the core region due to phase separation. Under the catalysis of molecular thermal motion, it gradually penetrates or erodes the amorphous region of the outer shell TPU, eventually causing macroscopic leakage from the micropores or weak defects of the fiber shell. This leads to a significant decrease in the long-term thermal cycling stability and encapsulation efficiency of the fiber membrane, making it unable to meet the long-term service requirements under dynamic deformations such as repeated bending and stretching.

[0006] Therefore, how to achieve multi-dimensional functional synergy of diamond, thermoplastic polyurethane and phase change materials in three-dimensional space, interface heat transfer and mechanical network under the dynamic flow field inducement of coaxial electrospinning, while ensuring high encapsulation rate and strong mechanical flexibility, and meeting the synergistic improvement of fiber thermal regulation, protection and photothermal performance, is a technical problem that urgently needs to be solved in the field of flexible phase change thermal management materials. Summary of the Invention

[0007] The purpose of this invention is to address the shortcomings of existing technologies by providing an NDs@PDA / TPU / PW coaxial phase change fiber membrane, its preparation method, and its applications. This invention solves the problems of easy leakage, low thermal conductivity, and limited functionality of existing organic phase change materials. It possesses excellent mechanical properties, UV blocking, waterproof and anti-fouling properties, and photothermal conversion performance, making it suitable for wearable protection, photothermal conversion, and energy management.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: The first aspect of this invention is to provide a method for preparing an NDs@PDA / TPU / PW coaxial phase change fiber membrane, comprising the following steps: Nanodiamonds and dopamine hydrochloride were added to a buffer solution in a certain ratio, and the resulting product was denoted as NDs@PDA. Disperse NDs@PDA into tetrahydrofuran and N,N Mix the dimethylformamide mixture thoroughly, then add thermoplastic polyurethane particles and mix thoroughly to obtain NDs@PDA / TPU shell spinning solution; Using octadecane solution as the inner spinning solution and the NDs@PDA / TPU shell spinning solution as the outer spinning solution, the solutions are simultaneously injected into the spinneret through coaxially arranged inner and outer needle tubes. An electric field is applied to the spinneret to perform coaxial electrospinning, so that the inner and outer spinning solutions together form a coaxial jet and are stretched into continuous fibers. After spinning is completed, the collected fibers are dried to obtain the NDs@PDA / TPU / PW coaxial phase change fiber membrane.

[0009] Furthermore, the mass ratio of the nanodiamond to dopamine hydrochloride is 2.5:1 to 1:1.

[0010] Furthermore, N,N The volume ratio of dimethylformamide to tetrahydrofuran is 1: (1:1.5).

[0011] Furthermore, the concentration of thermoplastic polyurethane in the NDs@PDA / TPU shell spinning solution is 17 wt.%~19 wt.%.

[0012] Furthermore, the concentration of NDs@PDA in the NDs@PDA / TPU shell spinning solution is 6 wt.%~8 wt.%.

[0013] Furthermore, the inner diameter of the inner needle tube is 20G~22G; the inner diameter of the outer needle tube is 17G~19G.

[0014] Furthermore, the injection rate of the outer spinning solution is 0.8 mL / h to 1.2 mL / h, and the injection rate of the inner spinning solution is 0.2 mL / h to 0.5 mL / h.

[0015] Furthermore, in the coaxial electrospinning process, the spinning voltage is 14 kV ~ 18 kV, the spinning distance is 10 cm ~ 20 cm, the roller speed is 300 r / min ~ 600 r / min, and the spinning time is 3 h ~ 5 h.

[0016] A second aspect of the present invention is to provide an NDs@PDA / TPU / PW coaxial phase change energy storage fiber membrane prepared by the method described above.

[0017] A third aspect of the present invention is to provide the application of the above-described NDs@PDA / TPU / PW coaxial phase change energy storage fiber membrane in the preparation of personal thermal management wearable textiles, outdoor ultraviolet protection materials or photothermal conversion energy storage materials.

[0018] Compared with the prior art, the beneficial effects of the technical solution provided by the present invention are as follows: (1) Based on coaxial electrospinning technology, this invention achieves deep synergy between diamond, TPU, and the phase change material n-octadecane in spatial, thermal, and mechanical dimensions: the dense and continuous TPU polymer network in the outer shell provides macroscopic physical confinement, confining the core phase change material within a one-dimensional micro-nano channel. Simultaneously, the micro- and nano-diamonds introduced into the core layer utilize their porous / surface active sites to microscopically adsorb and sterically confine the molten PCM molecules through interfacial capillary forces. Through this spatial three-dimensional synergistic mechanism of "coaxial macroscopic outer shell confinement + microscopic anchoring of diamond within the core," the composite membrane achieves an effective encapsulation rate of 40% loading, suppressing macroscopic phase separation of PCM during the phase change process, effectively solving the liquid leakage problem, and endowing the material with excellent encapsulation efficiency and thermal cycling stability. Furthermore, the fiber membrane exhibits excellent thermal cycling stability, with the latent heat of phase change remaining essentially unchanged after 50 thermal cycles.

[0019] (2) Under the combined action of high-voltage electric field stretching and fluid shear force during coaxial electrospinning, the high-hardness nanodiamond particles in the core layer self-assemble and oriented within the extremely fine core channels, constructing a continuous and efficient "thermal conduction pathway" along the fiber axis. Diamond, as an efficient heat collection and transport node, forms a low-thermal-resistance internal heat transfer network with the tightly bonded PCM. When dealing with sudden high heat flux densities, this thermal conduction network can overcome the thermal resistance barriers of traditional polymers and PCMs, rapidly capturing heat and quickly introducing and diffusing it along the axial pathway to the entire PCM core. This mechanism greatly alleviates the thermal resistance blind zone effect caused by crystal aggregation in traditional phase change materials, improving the thermal response speed of the phase change fiber membrane and effectively achieving a transient functional synergy of "high-speed heat conduction - high-efficiency heat storage". The coaxial fiber membrane prepared by this invention has a melting temperature of approximately 28.20℃, within the range of human thermal comfort; and a melting enthalpy as high as 95.23 J / g. The introduction of NDs@PDA improves thermal conductivity, resulting in a faster thermal response.

[0020] (3) The coaxial fiber membrane prepared by the present invention has excellent ultraviolet shielding performance (UPF>12000) in the shell layer by NDs@PDA, and can rapidly heat up and undergo phase change heat storage under simulated sunlight irradiation, with significant photothermal conversion and storage capabilities.

[0021] (4) This invention achieves functional modification of nanodiamonds by introducing a polydopamine coating (5-15 nm) on the surface of nanodiamonds, which significantly improves the dispersibility of nanodiamonds in polyurethane matrix, enhances the interfacial bonding force with polymer matrix, and overcomes the problems of easy agglomeration and poor compatibility of traditional inorganic fillers.

[0022] (5) The preparation process of the present invention is convenient, efficient and effective. Attached Figure Description

[0023] Figure 1 The graphs show the dispersibility and particle size analysis of NDs before and after modification in Example 1. Figure 2 Infrared spectrum, X-ray diffraction pattern and Raman spectrum of the fiber membrane prepared in Example 1; Figure 3 A scanning electron microscope image of the fiber membrane prepared in Example 1; Figure 4 The stress-strain curve of the fiber membrane prepared in Example 1; Figure 5 Photothermal performance diagram of the fiber membrane prepared in Example 1; Figure 6 SEM images (af) and fiber diameter distribution diagram (gl) of TPU / PW coaxial phase change fiber membranes with different core-shell flow rates. Figure 7 TEM images of TPU / PW coaxial phase change fiber membranes with different core-shell flow rates are shown. In the figures, a represents 0.2 mL / h, b represents 0.3 mL / h, c represents 0.4 mL / h, d represents 0.5 mL / h, e represents 0.6 mL / h, and f represents 0.7 mL / h. Figure 8 DSC curves for TPU / PW coaxial phase change fiber membranes with different core-shell flow rates and pure TPU uniaxial fiber membranes: (a) endothermic curve; (b) exothermic curve; Figure 9 SEM image (a) and TEM image (b) of TPU / PW coaxial phase change fiber with 7% NDs@PDA content prepared for Example 1; Figure 10 Infrared spectra of different samples prepared in Example 1 and Comparative Examples 1-3; Figure 11 Ultraviolet spectra of different samples prepared in Example 1 and Comparative Examples 1-3; Figure 12 XRD patterns of different samples prepared in Example 1 and Comparative Examples 1-3; Figure 13 The TG (a) and DTG curves (b) of different fiber membrane samples are shown. Figure 14DSC curves for different fiber membrane samples: (a) endothermic curve; (b) exothermic curve; Figure 15 50 thermal cycling tests on NDs@PDA / TPU / PW coaxial phase change fiber membrane; Figure 16 Comparison of UV-Vis spectra and UV protection performance (UPF values) of Example 1 and Comparative Examples 1-3; Figure 17 The image shows the photothermal conversion results of the NDs@PDA / TPU / PW coaxial phase change fiber membrane at an illumination intensity of 100 mW / cm². 2 Time: (a) Infrared image, (a1) Temperature change curve during heating, (a2) Temperature change curve during cooling; at a light intensity of 300 mW / cm² 2 Time: (b) Infrared image, (b1) Temperature change curve during heating, (b2) Temperature change curve during cooling; at a light intensity of 500 mW / cm² 2 Time: (c) Infrared image, (c1) Temperature change curve during heating, (c2) Temperature change curve during cooling. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the specific embodiments and accompanying drawings are described in further detail below. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0025] The present invention provides a method for preparing an NDs@PDA / TPU / PW coaxial phase change fiber membrane, comprising the following steps: S1. Surface functionalization modification of nanodiamonds (NDs): NDs and dopamine hydrochloride were added to Tris-HCl buffer in a certain ratio, stirred at high speed, centrifuged and washed, and the modified NDs were collected and denoted as NDs@PDA. S2. Prepare the electrospinning precursor solution by adding the NDs@PDA from step S1 to tetrahydrofuran and N,N The dimethylformamide mixture was ultrasonically mixed to obtain solution A. Thermoplastic polyurethane (TPU) was added to solution A and stirred evenly at room temperature to obtain NDs@PDA / TPU shell spinning solution. S3. Using n-octadecane (PW) as the core spinning solution; S4. Using coaxial electrospinning technology, the NDs@PDA / TPU shell spinning solution obtained in step S2 and the PW core spinning solution obtained in step S3 are placed in an injection device, and the outer needle and inner needle of the coaxial needle are connected respectively. The flow rate of the shell and core solutions is controlled by a micro-injection pump, and spinning is carried out under the condition of applying high voltage electrostatics. The fibers are received on the roller receiving device. S4. After spinning, the fiber membrane is placed in a vacuum drying oven for drying to remove residual solvent, thus obtaining the NDs@PDA / TPU / PW coaxial phase change energy storage fiber membrane.

[0026] In some embodiments, in step S1: NDs (50 ~ 100 nm) powder is ultrasonically dispersed in a prepared Tris-HCl buffer solution, and then dopamine hydrochloride is added. The resulting mixed solution is ultrasonically treated, covered with plastic wrap, and magnetically stirred at room temperature. The resulting suspension is centrifuged and washed three times with deionized water. The resulting gray-black powder is dried overnight in a drying oven to obtain NDs@PDA powder for further use.

[0027] Preferably, in step S1: the pH of the Tris-HCl buffer solution is 8.5; to ensure uniform deposition of polydopamine on its surface, the concentration of NDs in the buffer solution is controlled to be 2-5 mg / mL; the mass ratio of NDs powder to dopamine hydrochloride is 2.5:1-1:1; and the solution is sonicated for 10-30 min.

[0028] In some embodiments, in step S1, the reaction is carried out at room temperature for 20 h, the resulting suspension is washed three times with deionized water, the process is centrifuged at a speed of 6000 r / min, the drying temperature is 60 ~ 70 ℃, and the drying time is 15 ~ 24 h.

[0029] In some embodiments, in step S1, the polydopamine coating on the nanodiamond surface is 5 to 15 nm thick.

[0030] In some implementations, in step S2, N,N The volume ratio of dimethylformamide to tetrahydrofuran is 1:1 to 1.5, preferably 1:1. The two are ultrasonically mixed to obtain mixed solution A, with an ultrasonic power of 450 W to 650 W, preferably 500 W, and an ultrasonic time of 70 min.

[0031] In some embodiments, in step S2, 17 wt.%~19 wt.% of the NDs powder is relatively uniformly dispersed in the polymer spinning solution. The NDs powder is then magnetically stirred for 12 hours at a constant temperature of 25 °C and a rotation speed of 300 rpm until uniformly mixed with solution A.

[0032] In some embodiments, in step S3, the inner diameter of the coaxial needle is 20G~22G, preferably 21G, and the inner diameter of the outer needle is 17G~19G, preferably 18G.

[0033] In some embodiments, in step S3, to obtain the best morphology and coating effect, the injection rate of the outer spinning solution is 0.8 mL / h to 1.2 mL / h, preferably 1 mL / h; the injection rate of the inner spinning solution is 0.2 mL / h to 0.5 mL / h, preferably 0.5 mL / h.

[0034] In some embodiments, in step S3, during the coaxial electrospinning process, the spinning voltage is 14 kV ~ 18 kV, preferably 16 kV; the spinning distance is 10 cm ~ 20 cm, preferably 15 cm; the roller speed is 300 r / min ~ 600 r / min, preferably 500 r / min, and the spinning process is carried out at room temperature.

[0035] In some embodiments, in step S4, the drying temperature of the fiber membrane is 50°C to 60°C and the drying time is 10 h to 16 h. Preferably, the drying temperature is 50°C and the drying time is 12 h.

[0036] The invention has now been generally described, and will be more readily understood by referring to the following embodiments, which are provided by way of example and not by way of limitation.

[0037] The characterization methods used in this invention are as follows: Transmission Electron Microscope (TEM): The core-shell morphology of the fibers was characterized using a Thermofisher Scientific F200x TEM. The fibers were collected directly on a copper mesh during spinning, and their morphology was subsequently characterized under an accelerating voltage of 80 kV.

[0038] Differential Scanning Calorimetry (DSC): The thermal storage performance of coaxial phase change fibers was characterized using a TAQ2000 differential scanning calorimeter (DSC). First, 10 mg of sample was weighed and placed in a crucible. Under a nitrogen atmosphere, the temperature was set to 0–100 °C, and the heating / cooling rate was set to 10 °C / min. The phase change temperature and latent heat of phase change of the sample were calculated by analyzing the endothermic / exothermic peaks and integrating the area. The actual PW content in NDs@PDA / TPU / PW was then determined using the following formula: (1) X-ray diffraction (XRD): The crystal structure of TPU / PW and NDs@PDA / TPU / PW coaxial phase change fibers was characterized using a Bruker D8 Advance X-ray powder diffractometer (Germany). The scanning range was 10. ° - 60 ° The scanning speed is 5 ° / min.

[0039] Thermal cycling reliability testing: The thermal cycling stability of the NDs@PDA / TPU / PW coaxial phase change fiber membrane was tested using DSC. The heating and cooling rates were set to 10 ℃ / min, and the temperature range was set to 0~50 ℃. The thermal performance data of the phase change fiber membrane were recorded using DSC after 50 thermal cycles.

[0040] Photothermal performance characterization: The NDs@PDA / TPU / PW coaxial phase change fiber membrane was subjected to one standard sunlight exposure (100 mW / cm²) under AM1.5G standard spectral sunlight simulator SS-X180R. 2 ), 3 standard sunlight (300 mW / cm) 2 ) and 5 standard solar radiation (500 mW / cm) 2 Simulation. A 5×5 cm... 2 The nanofiber membrane was irradiated at a distance of 20 cm from the solar simulator for 5 min. Throughout the experiment, the surface temperature of the nanofiber membrane was monitored using an infrared thermal imager (FLUKE, TIX660), and its temperature change was collected every 30 s.

[0041] Tensile strength characterization: The mechanical properties of the fiber membrane were analyzed using an electronic universal testing machine (CMT6103). The test conditions for the fiber membrane were based on the ASTM-D638 standard method. Different regions of the same fiber membrane were cut into 10×60mm pieces. 2The test was conducted at a rate of 20 mm / min, and the average of five sets of data was used to evaluate the mechanical properties of the fiber membrane.

[0042] In previous research, this invention successfully prepared NDs@PDA / TPU uniaxial composite nanofibers. When the NDs@PDA doping concentration was 7%, the overall fiber morphology and properties of the NDs@PDA / TPU were within a good range. The research details are as follows: Experimental Group 1: (1) Nanodiamond (NDs, 50~100 nm) powder was ultrasonically dispersed in a Tris-HCl buffer solution with pH=8.5 at a concentration of 5 mg / mL. Dopamine hydrochloride was then added to control the mass ratio of NDs to NDs at 2.5:1. The reaction was carried out with magnetic stirring at room temperature for about 20 h. The resulting suspension was washed three times by centrifugation at 6000 r / min and then dried overnight at 60 ℃ to obtain surface-functionalized NDs@PDA powder.

[0043] (2) Weigh NDs@PDA and ultrasonically disperse it in a mixed solution of tetrahydrofuran and N,N-dimethylformamide (volume ratio 1:1) to prepare 20 g of NDs@PDA dispersion with a mass fraction of 1 wt.%. Ultrasonic power is 500 W and time is 70 min to obtain mixed solution A. Then add thermoplastic polyurethane (TPU), wherein the mass fraction of TPU relative to the mixed solution is 18 wt.%, and stir at 25 ℃ and 300 rpm for 12 h to obtain a uniform NDs@PDA / TPU spinning solution.

[0044] (3) Using electrospinning, the NDs@PDA / TPU spinning solution was transferred to a 10 mL microsyringe for spinning. The ambient temperature was controlled at 25℃±5 and the humidity at 45%±5. Under the conditions of spinning concentration and voltage (18 wt.% and 16 kV), spinning was carried out at room temperature for 8 h with a spinning distance of 15 cm, a feed speed of 1 mL / h and a roller speed of 500 r / min. The prepared fiber membrane was placed in a 60 ℃ oven for 1 h to allow the solvent on the fiber surface to evaporate fully, and finally a nanodiamond-based flexible fiber membrane containing 1 wt.% NDs@PDA was obtained.

[0045] Experimental Group 2: Basically the same as Experimental Group 1, except that 20 g of NDs@PDA dispersion with a mass fraction of 3 wt.% was prepared to obtain a flexible fiber membrane containing 3 wt.% NDs@PDA.

[0046] Experimental Group 3: Basically the same as Experimental Group 1, except that 20 g of NDs@PDA dispersion with a mass fraction of 5wt.% was prepared to obtain a flexible fiber membrane containing 5wt.% NDs@PDA.

[0047] Experimental Group 4: Basically the same as Experimental Group 1, except that 20 g of NDs@PDA dispersion with a mass fraction of 7wt.% was prepared to obtain a flexible fiber membrane containing 7wt.% NDs@PDA.

[0048] Experimental Group 5: Basically the same as Experimental Group 1, except that 20 g of NDs@PDA dispersion with a mass fraction of 9wt.% was prepared to obtain a flexible fiber membrane containing 9wt.% NDs@PDA.

[0049] Experimental Group 6: Basically the same as Experimental Group 1, except that no nanodiamonds were added. Thermoplastic polyurethane was dissolved in a mixed solution of tetrahydrofuran and N,N-dimethylformamide (mass ratio 1:1), and stirred at 25 °C for 12 h to obtain a uniform electrospinning solution with a mass fraction of 18 wt.%.

[0050] The surface-functionalized nanodiamond-based composite fiber membranes prepared in experimental groups 1-5 were characterized at both macroscopic and microscopic levels. The specific results are as follows: like Figure 1 As shown, the dispersibility and particle size analysis results were obtained. NDs and NDs@PDA were ultrasonically dispersed in a mixed solution of DMF and THF and allowed to stand for 24 h. The dispersion stability of NDs@PDA in the solution was significantly better than that of unmodified NDs. The particle size distribution results showed that the particle size of NDs modified with polydopamine was significantly increased, further confirming the successful encapsulation of PDA.

[0051] like Figure 2 As shown in figure a, the infrared spectrum results show that, compared with unmodified NDs, NDs@PDA at 3371 cm⁻¹ -1 A broad absorption peak appears at 1610 cm⁻¹, corresponding to the stretching vibrations of OH and NH on the PDA; and at 1610 cm⁻¹... -1 An absorption peak for aromatic C=C stretching vibrations appears at 1513 cm⁻¹. -1 and 1260 cm -1 Absorption peaks of C=N and CN appeared at the respective locations, indicating that surface PDA has been successfully modified onto the NDs surface.

[0052] like Figure 2 As shown in b, the X-ray diffraction results show that both NDs before and after modification exhibit obvious diffraction peaks at 43.98° and 75.36°, indicating that PDA modification did not change the original cubic crystal structure of NDs and maintained its crystal integrity.

[0053] like Figure 2As shown in c, by comparing the peak intensity ratio (ID / IG) of the D and G bands, it was found that the peak intensity ratio of NDs@PDA was significantly higher than that of unmodified NDs, and the surface PDA coating effectively improved the surface functionalization of NDs.

[0054] like Figure 3 As shown, the fiber morphology results show that as the mass fraction of NDs in the fiber membrane increases, the average diameter of the composite fiber membrane gradually increases, and the surface roughness also increases accordingly, indicating that the addition of NDs has a regulatory effect on fiber morphology.

[0055] like Figure 4 As shown, the mechanical properties are as follows: with the increase of NDs mass fraction in the fiber membrane, the Young's modulus, tensile strength and elongation at break of the composite fiber membrane gradually increase. Compared with pure TPU fiber membrane, the above properties are increased by up to 39.42%, 133.33% and 48.21%, respectively.

[0056] like Figure 5 As shown, the air permeability results show that as the mass fraction of NDs in the fiber membrane increases, the air permeability of the composite fiber membrane gradually decreases from 94.9 mm / s to 52.9 mm / s. Although the air permeability decreases with the increase of filler content, the value of all samples remains above 50 mm / s, and the surface material itself still maintains good gas permeability, belonging to the category of typical air permeable materials.

[0057] The results of the water contact angle show that as the mass fraction of NDs in the fiber membrane increases, the water contact angle of the composite fiber membrane increases from 101.4° to 137.5°, which indicates that it is a hydrophobic material.

[0058] With the increase of NDs mass fraction in the fiber membrane, the UPF value can reach up to 14114.86, which is more than 100 times higher than that of pure TPU fiber membrane.

[0059] As the mass fraction of NDs in the fiber membrane increases, the heating rate of the composite fiber membrane under light irradiation shows a gradual increasing trend. It can convert absorbed light energy into heat energy, achieve uniform heat distribution inside the material, and has a certain photothermal conversion capability.

[0060] Since the flow rates of the shell and core layers during coaxial electrospinning affect the core-shell structure and thickness of the fiber, TPU / PW coaxial phase change fibers with different core-shell flow rate ratios were prepared to screen out a suitable core-shell flow rate ratio and to investigate the effect of the liquid feed rate on the microstructure and internal PW content of the phase change fibers.

[0061] Weigh a certain mass of TPU particles and disperse them in a mixed solvent of DMF and THF. V DMF :VTHF In a 1:1 ratio, TPU was completely dissolved at room temperature under magnetic stirring at 800 rpm to prepare an 18 wt.% TPU precursor solution as the shell electrospinning solution. Using a coaxial needle with an inner diameter of 21G and an outer diameter of 18G, the TPU precursor solution and PW solution were placed in two 10 mL syringes as the shell and core layers, respectively. The flow rates of the shell and core layer solutions were controlled by two micro-injection pumps. During spinning, the spinning voltage was 16 kV, the spinning distance was 15 cm, the roller speed was 500 r / min, and spinning was carried out at room temperature for 8 h. After spinning, the solution was placed in a vacuum drying oven at 50 ℃ for 12 h. The parameters for the shell and core layer feed rates are shown in Table 1.

[0062] Table 1. Preparation of TPU / PW fiber membranes at different core-shell propulsion velocities.

[0063]

[0064] When using a 18 wt.% TPU solution for uniaxial electrospinning, the fiber surface is smooth and the diameter is uniform. However, when using the same parameters for coaxial electrospinning, the fiber morphology varies depending on the core-shell flow rate ratio. For example... Figure 6 The image shows SEM images and fiber diameter distributions of TPU / PW coaxial phase change fiber membranes with different core-shell flow rate ratios. From the SEM images, it can be seen that ( Figure 6 As shown in Figure af), the fibers prepared by coaxial electrospinning have a good overall fiber structure and are free of beads. However, when the core layer advance speed increases to 0.6~0.7 mL / h, the PW cannot be well coated by the shell polymer solution, and the Taylor cone at the spinning needle becomes unstable, resulting in multiple jets and causing uneven fiber thickness and mutual adhesion. When the core layer solution can be stably coated by the shell, the excessively fine fibers disappear, indicating that the difference in advance speed between the core and shell determines the stability of the Taylor cone. This can be seen from the fiber diameter distribution diagram (…). Figure 6 As shown in gl), under the condition of maintaining a shell layer advance rate of 1 mL / h and a core layer advance rate set at 0.2~0.8 mL / h, the average diameters of the TPU / PW fiber membranes were 0.694 ± 0.181 μm, 1.185 ± 0.182 μm, 1.376 ± 0.334 μm, 1.588 ± 0.310 μm, 1.193 ± 0.462 μm, and 0.610 ± 0.344 μm, respectively. When the core layer advance rate was 0.2, 0.3, 0.4, and 0.5 mL / h, the coaxial fiber diameter gradually increased with the increase of the core layer flow rate, indicating that more PW was encapsulated in the phase change fiber. Therefore, core layer advance rates of 0.6 mL / h and 0.7 mL / h are not suitable for preparing core-shell phase change fibers.

[0065] like Figure 7 The image shown is a TEM image of TPU / PW coaxial phase change fiber membranes with different core-shell flow rate ratios. From... Figure 7 As can be seen in the data, when the core layer propagation rate is 0.2, 0.3, 0.4, and 0.5 mL / h, the core-shell structure of the fiber becomes clearly visible, and the core layer thickness gradually increases while the shell layer thickness decreases with increasing flow rate. However, when the core layer propagation rate is 0.6 mL / h and 0.7 mL / h, the core-shell structure is barely visible, indicating that the encapsulation effect is not ideal. This further confirms that at core layer propagation rates of 0.6 mL / h and 0.7 mL / h, TPU cannot effectively encapsulate PW in the fiber core layer. Moreover, increasing the core layer propagation rate allows the phase change fiber to achieve a higher PW content.

[0066] To further explore the optimal core-shell propulsion velocity ratio of coaxial phase change fibers, this invention uses DSC technology to test the thermal storage performance of TPU / PW coaxial phase change fiber membranes, such as... Figure 8 The figures show the DSC endothermic and exothermic curves of TPU / PW coaxial phase change fiber membranes with different core-shell flow rates and pure TPU uniaxial fiber membranes, respectively. As can be seen from the figures, pure TPU uniaxial fibers did not show obvious endothermic or exothermic peaks throughout the entire test temperature range, indicating that TPU, as the shell material, does not possess phase change heat storage capacity itself, but only serves as structural support and encapsulation. In contrast, the other TPU / PW coaxial phase change fibers with different core-shell flow rates all exhibited clear and repeatable endothermic and exothermic peaks during heating and cooling, indicating that n-octadecane (PW) can undergo a stable and reversible solid-liquid phase change inside the fiber, verifying the effective encapsulation of the phase change material by the coaxial structure. The thermophysical parameters of the TPU / PW coaxial phase change fibers calculated from the endothermic and exothermic curves are shown in Table 2, including the melting / crystallization temperature (Tm / Tc) and the latent heat of melting / crystallization phase change (ΔHm / ΔHc). As the core layer propulsion speed increases, the latent heat of fusion ΔHm of the TPU / PW fiber membrane decreases from 24.57 J·g. -1 The value was increased sequentially to 54.38 J·g. -1 63.93 J·g -1 and 84.83 J·g -1Based on the aforementioned SEM results, it can be seen that with the increase of the core layer propulsion velocity, the fiber diameter and core layer volume fraction increase accordingly, resulting in an increase in the PW content of the phase change material encapsulated in the core layer, thereby endowing the fiber membrane with higher heat storage capacity. Simultaneously, it was observed that the melting temperature (Tm) and crystallization temperature (Tc) of the fiber membrane shifted to a certain extent towards lower temperatures. This indicates that the increase in fiber diameter alters the interaction environment between the polymer chain segments inside the fiber and the phase change material, affecting the crystallization behavior of the phase change material. This leads to faster and denser formation of the crystalline structure of the polymer chains, enabling the phase change process to be completed at relatively lower temperatures.

[0067] Table 2. Thermophysical parameters of TPU / PW coaxial phase change fiber membranes with different core-shell flow rates.

[0068]

[0069] Example 1 This embodiment provides an NDs@PDA / TPU / PW coaxial phase change fiber membrane and its preparation method. Details are as follows: (1) Nanodiamond (NDs, 50~100 nm) powder was ultrasonically dispersed in a Tris-HCl buffer solution with pH=8.5 at a concentration of 5 mg / mL. Dopamine hydrochloride was then added to control the mass ratio of NDs to NDs at 2.5:1. The reaction was carried out with magnetic stirring at room temperature for about 20 h. The resulting suspension was washed three times by centrifugation at 6000 r / min and then dried overnight at 60 ℃ to obtain surface-functionalized NDs@PDA powder.

[0070] (2) Preparation of spinning solution: Weigh NDs@PDA and ultrasonically disperse it in a mixed solution of tetrahydrofuran and N,N-dimethylformamide (volume ratio 1:1) to prepare 20 g of NDs@PDA dispersion with a mass fraction of 7 wt.%. Ultrasonic power is 500 W and time is 60 min. Then, thermoplastic polyurethane (TPU) is added to the above solution, wherein the mass fraction of TPU relative to the mixed solution is 18 wt.%. The mixture is magnetically stirred at 25 ℃ and 800 rpm for 24 h to fully disperse NDs@PDA in the solution, thus obtaining NDs@PDA / TPU shell solution.

[0071] (3) Prepare n-octadecane solution (PW) as the core layer solution.

[0072] (4) Coaxial electrospinning process for preparing composite fibers: Using a coaxial needle with an inner diameter of 21G and an outer diameter of 18G, NDs@PDA / TPU solution and PW solution were placed in two 10 ml syringes as the shell and core layers, respectively. The flow rates of the shell and core layer solutions were controlled by two micro-injection pumps. Under the condition of obtaining the optimal core-shell propulsion speed, i.e., the shell propulsion speed was set to 1.0 ml / h, the core propulsion speed to 0.5 ml / h, the spinning voltage to 16 kV, the spinning distance to 15 cm, and the roller speed to 500 r / min, spinning was carried out at room temperature for 8 h.

[0073] (3) Drying the coaxial fiber membrane: After the spinning is finished, place it in a vacuum drying oven at 50 ℃ for 12 hours.

[0074] Comparative Example 1 (1) Preparation of spinning solution: The difference from Example 2 is that no nanodiamonds were added to the spinning precursor solution. Thermoplastic polyurethane was dissolved in a mixed solution of tetrahydrofuran and N,N-dimethylformamide (mass ratio 1:1) and stirred at 25°C for 12 h to obtain a uniform shell electrospinning solution with a mass fraction of 18 wt.%. PW solution was still prepared as the core layer solution.

[0075] (2) Coaxial electrospinning process for preparing composite fibers: Using a coaxial needle with an inner diameter of 21G and an outer diameter of 18G, TPU precursor solution and PW solution were placed in two 10 ml syringes as the shell and core layers, respectively. The flow rates of the shell and core layer solutions were controlled by two micro-injection pumps. During the spinning process, the shell layer advance speed was set to 1.0 ml / h, the core layer advance speed to 0.5 ml / h, the spinning voltage to 16 kV, the spinning distance to 15 cm, and the roller speed to 500 r / min. Spinning was carried out at room temperature for 8 h.

[0076] (3) Drying the coaxial fiber membrane: After the spinning is finished, place it in a vacuum drying oven at 50 ℃ for 12 hours.

[0077] Comparative Example 2 (1) The difference between this and Example 2 is that no nanodiamonds were added to the spinning precursor solution and uniaxial fibers were prepared. Thermoplastic polyurethane was dissolved in a mixed solution of tetrahydrofuran and N,N-dimethylformamide (mass ratio 1:1) and stirred at 25 °C for 12 h to obtain a uniform TPU electrospinning solution with a mass fraction of 18 wt.%.

[0078] (2) Preparation of composite fibers by uniaxial electrospinning: Using a uniaxial 21G needle, the precursor solution was transferred to a 10 mL microsyringe for spinning. The feed rate was adjusted to 1 ml / h, the spinning voltage was 16 kV, the spinning distance was 15 cm, the roller speed was 500 r / min, and spinning was carried out at room temperature for 8 h.

[0079] (3) Drying the uniaxial fiber membrane: After the spinning is finished, place it in a vacuum drying oven at 50 ℃ for 12 hours.

[0080] Comparative Example 3 (1) The difference between this and Example 2 is that only the shell solution is used for uniaxial fiber preparation. A certain mass of NDs@PDA is weighed and dispersed in a mixed solvent of DMF and THF (volume ratio 1:1) and ultrasonically treated for 1 h to ensure uniform mixing with the solvent. Then TPU is added to the above solution and magnetically stirred at 800 rpm for 24 h at room temperature to ensure that NDs@PDA is fully dispersed in the solution, thus obtaining the NDs@PDA / TPU precursor solution.

[0081] (2) Preparation of composite fibers by uniaxial electrospinning: Using a uniaxial 21G needle, the precursor solution was transferred to a 10 mL microsyringe for spinning. The feed rate was adjusted to 1 ml / h, the spinning voltage was 16 kV, the spinning distance was 15 cm, the roller speed was 500 r / min, and spinning was carried out at room temperature for 8 h.

[0082] (3) Drying the uniaxial fiber membrane: After the spinning is finished, place it in a vacuum drying oven at 50 ℃ for 12 hours.

[0083] The coaxial and uniaxial composite fiber membranes prepared in the above embodiments and comparative examples were characterized at both macroscopic and microscopic levels. The specific results are as follows: (1) The fiber morphology results in the examples are as follows Figure 9 As shown. Figure 9 Figure 'a' shows the SEM morphology of TPU / PW coaxial phase change fibers with a content of 7% NDs@PDA. It can be seen that particle protrusions appear on the surface of the fiber membrane prepared after adding NDs@PDA, indicating that the modified nanodiamonds were successfully incorporated and participated in the fiber forming process. Meanwhile, compared with the coaxial phase change fibers without NDs@PDA, the overall diameter of the composite fiber is significantly reduced, and the fiber diameter distribution tends to be finer, with an average diameter of 1.021±0.193μm. This is mainly related to the fact that the addition of NDs@PDA changes the conductivity of the spinning precursor solution, etc., which enhances the stretching effect of the jet under the combined action of electrostatic repulsion and surface tension during electrospinning, resulting in instability. Secondary or even multi-stage jets are ejected from the Taylor cone surface, further refining the fiber diameter. Figure 9 Image b in the figure is a TEM image of the NDs@PDA / TPU / PW coaxial phase change fiber. The core region is n-octadecane (PW), and the outer shell is an NDs@PDA / TPU composite layer. The interface distribution is continuous and clear. When the shell thickness is 1.148 μm, the core layer thickness reaches 0.927 μm, indicating that the coaxial electrospinning process can effectively encapsulate the phase change material. Furthermore, since the prepared NDs@PDA is rich in polar functional groups such as hydroxyl groups, it exhibits good dispersibility in the DMF solvent system. Therefore, no obvious large-scale aggregation was observed in the shell layer, and the overall distribution within the fiber is relatively uniform, providing a stable structural basis for subsequent phase change heat storage and thermal regulation performance.

[0084] (2) To verify the effective encapsulation of PW in coaxial phase change fibers, infrared spectroscopy analysis was performed on different samples, and the results are as follows: Figure 10 As shown. Pure TPU fiber membrane at 3339 cm⁻¹. -1 and 1530 cm -1 Characteristic peaks of stretching and bending vibrations of NH bonds can be observed at 1727 cm⁻¹. -1 and 1075 cm -1 The characteristic peaks at these locations correspond to the stretching vibrations of the carbonyl group (C=O) and the stretching vibrations of the asymmetric COC bond in the polyurethane molecule, respectively. These characteristic peaks for NH, NH, and COC also appear in the infrared spectra of TPU / PW and NDs@PDA / TPU / PW fiber membranes, indicating that the TPU shell is structurally stable in the composite fiber. For n-octadecane, its characteristic peak is located at 2918 cm⁻¹. -1 and 2848 cm -1 Corresponding to the asymmetric and symmetric stretching vibrations of CH, respectively, located at 1469 cm⁻¹ -1 and 717 cm -1 The characteristic peaks at these locations correspond to the bending vibration peak and the in-plane rocking vibration peak of -CH2, respectively. These characteristic peaks representing PW are clearly visible in the infrared spectrum of NDs@PDA / TPU / PW, indicating that PW has been successfully encapsulated into the core layer of the coaxial fiber, and that the NDs@PDA / TPU / PW fiber membrane exhibits good performance at 1600 cm⁻¹. -1 The intensity of the characteristic peak representing the C=C vibration of the benzene ring skeleton in NDs@PDA was enhanced. This confirms the stable encapsulation of n-octadecane and the successful fabrication of the NDs@PDA / TPU / PW coaxial phase change fiber membrane.

[0085] (3) such as Figure 11The UV-Vis absorption spectral analysis of pure TPU, TPU / PW, and NDs@PDA / TPU / PW composite nanofiber membranes is shown. Significant absorption differences are observed among the different samples in the 200–300 nm spectral range. The pure TPU fiber membrane without NDs@PDA doping exhibits low UV absorption intensity in the UV region, indicating limited shielding ability against UV light. The addition of PW does not significantly enhance the UV absorption of the fiber membrane, suggesting that PW contributes little to UV absorption. In contrast, NDs@PDA / TPU / PW exhibits significant UV absorption intensity across the entire UV band, with levels similar to those of uniaxial NDs@PDA / TPU fibers. This demonstrates that NDs@PDA doping endows the TPU / PW coaxial phase change fiber membrane with excellent UV protection performance without affecting the encapsulation structure of the phase change material, providing theoretical support for its application in UV-protective wearable textiles and outdoor protective materials.

[0086] (4) such as Figure 12 As shown. Pure n-octadecane (PW) exhibits typical high crystallinity characteristics, with characteristic diffraction peaks corresponding to the α-phase crystal structure visible at 11.02° (003), 14.85° (004), 38.79° (022) and 43.57° (207), and at 18.74° (010), 21.34° (011), 22.68° (100), 24.80° (111) and 34.24° (207). The diffraction peak at (110) corresponds to the β-phase crystal structure

[132] . In the XRD curve of the NDs@PDA / TPU / PW composite fiber membrane, most of the main β-phase characteristic peaks of PW in the range of 19°~25° and the (111) peak of NDs@PDA at 43.98° are retained, while the peak corresponding to the α-phase crystal structure almost disappears due to the encapsulation of the TPU shell. Therefore, the above XRD results prove the successful loading of core paraffin and nanodiamond, and the stable coexistence of TPU, PW and NDs@PDA in the coaxial structure.

[0087] (5) such as Figure 13As shown, the initial decomposition temperature of n-octadecane is approximately 129.7 °C, and it completely decomposes at 198.5 °C. The thermal decomposition of pure TPU fiber membranes mainly occurs in the 320–450 °C range, corresponding to the gradual decomposition of the hard and soft segments. For coaxial TPU / PW0.5 and NDs@PDA / TPU / PW composite fiber membranes, the pyrolysis process of both mainly includes two stages: the first stage, in the temperature range of 150–250 °C, corresponds to the decomposition of n-octadecane, with mass losses of 32.8% and 34.70%, respectively, corresponding to the PW content in the coaxial fibers; the second stage, in the temperature range of 320–500 °C, corresponds to the thermal decomposition of the shell TPU and NDs@PDA. Furthermore, the mass residue rate of NDs@PDA / TPU / PW at 700 °C (9.7%) is significantly higher than that of the undoped sample (4.8%), further demonstrating that the doping of nanodiamonds can improve the overall thermal stability of the coaxial fiber membrane.

[0088] (6) The thermal storage performance of the composite fiber membrane, i.e., the comparison of DSC endothermic and exothermic curves, is shown in the figure below. Figure 14 As shown, its heat absorption / release curves and thermophysical parameters are shown in Table 3. For the NDs@PDA / TPU / PW composite fiber membrane, its melting temperature ( T m The melting temperature of the composite fiber was 28.20 °C, close to that of pure PW (28.12 °C), indicating that the composite fiber perfectly preserved the phase transition temperature range of n-octadecane, which is suitable for human thermal comfort. Compared with undoped TPU / PW coaxial fibers, the melting temperature of the NDs@PDA / TPU / PW composite fiber film showed a trend towards lower temperatures. This is mainly attributed to the high thermal conductivity of NDs@PDA, which effectively promotes heat transfer between the shell and core layers of the phase change fiber, allowing the core PW to respond to external temperature changes and undergo phase transition earlier and more quickly. Simultaneously, the latent heat of TPU / PW also increased to some extent after the addition of NDs@PDA, resulting in a higher enthalpy of fusion (…). ΔH m ) and enthalpy of crystallization ( ΔH c The enthalpy values ​​reached 95.2 J / g and 93.3 J / g, respectively. Based on the melting enthalpy of pure PW (241.88 J / g), the effective encapsulation efficiency of this composite fiber membrane for phase change materials is approximately 40%.

[0089] Table 3. Thermophysical parameters of different samples.

[0090]

[0091] (7) To evaluate the cyclic thermal stability of the NDs@PDA / TPU / PW fiber membrane, 50 consecutive DSC tests were conducted within a temperature range of 0–50 °C. The results showed that the phase transition temperature and latent heat of phase transition remained almost constant (e.g., Figure 15 As shown in the figure, the phase change fiber membrane exhibits good thermal cycling stability.

[0092] (8) As shown in Table 4, the tensile strength of the NDs@PDA / TPU / PW composite film is 10.80 MPa, and the elongation at break is 317.28%. This is 1.85 times that of the pure TPU film, and the elongation at break remains above 300%. This suggests that adding NDs@PDA to the shell may increase the viscosity of the spinning solution, which in turn increases the fiber diameter. As a result, the thickness of the fiber film accumulated in the same time increases, thus increasing the tensile strength of the fiber.

[0093] Table 4. Tensile strength and elongation at break of different fiber membranes.

[0094]

[0095] (9) Results of UV protection as follows Figure 16 As shown, both pure TPU and undoped NDs@PDA coaxial TPU / PW fiber films exhibit high transmittance in both the UV-A and UV-B bands, with corresponding UPF values ​​of only around 70. This indicates that the single polymer matrix and phase change material (n-octadecane) cannot provide effective radiation shielding against ultraviolet light. However, after introducing functional fillers, the UV-A and UV-B transmittance of the coaxial NDs@PDA / TPU / PW composite fiber film decreases to below 0.1% and nearly 0%, respectively, while the UPF value reaches over 12000. This is mainly attributed to the excellent ultraviolet light absorption capacity of NDs@PDA in the shell. Furthermore, the ultraviolet protection performance of this coaxial composite film is on the same order of magnitude as that of uniaxial NDs@PDA / TPU fibers, and all indicators far exceed the national standard GB / T18830-2009. This confirms that the coaxial structure design successfully achieves excellent ultraviolet shielding capabilities while realizing phase change temperature regulation through a functionalized shell.

[0096] (10) The results of photothermal conversion are as follows Figure 17 As shown, the results illustrate different light intensities (100 mW / cm²). 2 300mW / cm 2 500 mW / cm 2 Infrared thermographic images and time-temperature profiles of NDs@PDA / TPU / PW coaxial phase change fiber membranes. As the light intensity increases from 100 mW / cm²... 2 Increased to 500 mW / cm 2At these temperatures, the surface equilibrium temperatures of the fiber membrane reached 44 ℃, 80 ℃, and 114 ℃, respectively, indicating that its equilibrium temperature increases significantly with increasing light intensity. Simultaneously, the NDs@PDA / TPU / PW coaxial phase change fiber membrane also exhibited a certain phase change capability, with a significant phase change process observed in the range of 25~29 ℃, consistent with the DSC test results. (At 100 mW / cm²) 2 Taking the results under light intensity as an example, the temperature of the fiber membrane rises rapidly within the first 3 seconds. When the temperature reaches 25~29 ℃, a plateau period of temperature rise occurs, namely the melting and absorption process. Figure 17 As shown in a1), this corresponds to the phase transition temperature of the PW. After the phase transition, the temperature continues to rise, reaching the saturation temperature at around 25 s. This process demonstrates that the fiber membrane can effectively convert solar energy into thermal energy and store it in the core layer PW. When the light source is removed, the fiber membrane shows a second temperature plateau when the temperature drops to approximately 28 °C, i.e., the exothermic crystallization process. Figure 17 As shown in a2), this indicates that it slows down the cooling rate and demonstrates a certain thermal buffering effect.

[0097] At 300 mW / cm 2 Simulated photothermal conversion and phase change energy storage behavior under sunlight irradiation. Infrared thermal image ( Figure 17 Figures b1 and b2 visually demonstrate that during the heating phase (0–15 s), the material's surface temperature rapidly rises from deep blue (room temperature) to a high orange-red state due to the excellent photothermal effect of NDs@PDA. During the cooling phase (300–450 s) after the light source is removed, the material's heat gradually dissipates to the environment and eventually returns to room temperature. Combined with the corresponding temperature-time curves, the heating curve (Figure b1) shows a plateau region with a gradually decreasing slope within 3–6 s (approximately 45°C–55°C), confirming that the phase change material (PW) inside the composite film undergoes a solid-liquid phase transition and stores energy in the form of latent heat. In the cooling curve (Figure b2), within the 330–420 s range, the material exhibits a significant isothermal plateau period of up to 90 seconds (approximately 28°C–30°C), which is due to the PW undergoing a liquid-solid reverse phase transition and continuously releasing latent heat. This graph fully demonstrates that the fiber membrane has successfully integrated high-efficiency "photo-thermal conversion" with intelligent "phase change temperature control / thermal management" functions.

[0098] At 500 mW / cm 2 Simulated photothermal conversion and phase change energy storage behavior under sunlight irradiation. Infrared thermal image ( Figure 17Figures c1 and c2 visually demonstrate that during the heating phase (0–10 s), the material's surface temperature rapidly increases thanks to the efficient photon capture capability of the NDs@PDA network, reaching a high temperature of nearly 114°C in just 10 seconds. Combined with the corresponding heating curve (Figure c1), even under such a high-flux heat, a identifiable sluggish slope region still appears in the 2–5 s period, confirming that the internally encapsulated phase change material (PW) can stably absorb and store latent heat through solid-liquid phase transition, providing a microscopic buffer against localized temperature rise. During the cooling phase (300–500 s) after the initial rapid dissipation, the cooling curve (Figure c2) exhibits a significant isothermal release plateau lasting 80 seconds in the 380–460 s range. Relying on the liquid-solid reverse phase transition of the PW to release latent heat, the temperature is precisely anchored at approximately 28–30°C. The thermal response data under high light intensity fully verifies that the fiber membrane not only has an excellent upper limit for high photothermal conversion, but also that its internal intelligent phase change temperature regulation mechanism still exhibits extremely high structural stability and temperature control robustness under extreme heat loads.

[0099] Due to the excellent light absorption and thermal conductivity of NDs@PDA, it can be concluded that solar energy can be absorbed and converted into heat energy through the molecular thermal vibrations of NDs@PDA. The π electrons in its molecular structure, after absorbing incident photons with sufficient energy, transition from the ground state to an excited state. Subsequently, the excited electrons return to the ground state through a non-radiative relaxation (vibrational-electron coupling) mechanism, releasing the absorbed light energy as heat energy. This heat energy is then stored and utilized through the solid-liquid phase transition of the core layer PW. Furthermore, with increasing light intensity, the visible fiber membrane's phase transition plateau time shortens, indicating that more heat is stored in the phase change fiber membrane, improving the efficiency of phase change energy storage. These results demonstrate the broad application prospects of NDs@PDA / TPU / PW coaxial phase change fiber membranes in the fields of photothermal conversion and phase change thermal storage.

[0100] Where there is no conflict, the above embodiments and features described herein can be combined with each other.

[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing an NDs@PDA / TPU / PW coaxial phase change fiber membrane, characterized in that, Includes the following steps: Nanodiamonds and dopamine hydrochloride were added to a buffer solution in a certain ratio, and the resulting product was denoted as NDs@PDA. Disperse NDs@PDA into tetrahydrofuran and N,N Mix the dimethylformamide mixture thoroughly, then add thermoplastic polyurethane particles and mix thoroughly to obtain NDs@PDA / TPU shell spinning solution; Using octadecane solution as the inner spinning solution and the NDs@PDA / TPU shell spinning solution as the outer spinning solution, the solutions are simultaneously injected into the spinneret through coaxially arranged inner and outer needle tubes. An electric field is applied to the spinneret to perform coaxial electrospinning, so that the inner and outer spinning solutions together form a coaxial jet and are stretched into continuous fibers. After spinning is completed, the collected fibers are dried to obtain the NDs@PDA / TPU / PW coaxial phase change fiber membrane.

2. The preparation method according to claim 1, characterized in that, The mass ratio of nanodiamond to dopamine hydrochloride is 2.5:1 to 1:

1.

3. The preparation method according to claim 1, characterized in that, N,N The volume ratio of dimethylformamide to tetrahydrofuran is 1: (1:1.5).

4. The preparation method according to claim 1, characterized in that, The concentration of thermoplastic polyurethane in the NDs@PDA / TPU shell spinning solution is 17 wt.%~19 wt.%.

5. The preparation method according to claim 1, characterized in that, The concentration of NDs@PDA in the NDs@PDA / TPU shell spinning solution is 6 wt.%~8 wt.%.

6. The preparation method according to claim 1, characterized in that, The inner diameter of the inner needle tube is 20G~22G; the inner diameter of the outer needle tube is 17G~19G.

7. The preparation method according to claim 1, characterized in that, The injection rate of the outer spinning solution is 0.8 mL / h to 1.2 mL / h, and the injection rate of the inner spinning solution is 0.2 mL / h to 0.5 mL / h.

8. The preparation method according to claim 1, characterized in that, During coaxial electrospinning, the spinning voltage is 14 kV ~ 18 kV, the spinning distance is 10 cm ~ 20 cm, the roller speed is 300 r / min ~ 600 r / min, and the spinning time is 3h ~ 5h.

9. An NDs@PDA / TPU / PW coaxial phase change energy storage fiber membrane prepared by the method according to any one of claims 1 to 8.

10. The application of the NDs@PDA / TPU / PW coaxial phase change energy storage fiber membrane as described in claim 9 in the preparation of personal thermal management wearable textiles, outdoor ultraviolet protection materials or photothermal conversion energy storage materials.